The Influence of Seasonal Allergic Conjunctivitis and Its Treatment on Choroidal Vascular Index - Neslihan Sevimli; Ümit Çallı; Fatin Çoban (Oftalʹmologiâ, 2023)
Purpose: To evaluate the the effects of seasonal allergic counjunctivitis (AC) and its treatment upon choroidal structure such as choroidal thickness (ChT) and choroidal vascular index (CVI) through the use of topical antihistamine agents. Methods. The 60 eyes of 30 patients were included in the AC group. Another 30 patients were included in the control group. The choroid was imaged by using enhanced depth imaging optical coherence tomography (EDI-OCT) instrument without pupillary dilation. ChT was defined as the area between the outer hyperreflective border of the RPE and the sclerochoroidal border at the fovea, 750 µm temporal to the fovea and 750 µm nasal to the fovea. Image J was used to measure CVI. With the images obtained from EDI-OCT, the total choroidal area (TCA), luminal area (LA), stromal area (SA), and CVI were calculated using the binarization method. Results. The mean ChT value in the AC group was 358.5 ± 93.8 µm at baseline and 356.8 ± 86.6 µm following 1 month of treatment. Meanwhile, the mean ChT in the control group was 316.6 ± 60.7 µm. The mean CVI value was 66.65 ± 2.98 in the control group, 70.75 ± 3.26 in the AC group at baseline, and 69.50 ± 3.17 following 1 month of treatment. Statistically significant difference was tracked between control and AC group (p = 0.028) and control group and posttreatment values (p=0,031). There were no statistically significant difference between initial AC treatment values and posttreatment values for all of the measurements. Conclusion. ChT and CVI can increase in patients with AC due to inflammation and increased vascular permeability. Although symptoms and signs related to AC may disappear after the treatment, effects in the choroid do not immediately normalize.